Natural capital accounting of cultivated land based on three-dimensional ecological footprint model-- A case study of the Beijing-Tianjin-Hebei region - Zhang, Hui; Zhu, Dao-Lin; Zhang, Yuanjie (Frontiers in Environmental Science, 2022)
The fairness of the utilization of cultivated land resources is essential for the balanced development of the region, but there are few papers to analyze it. Against the background of the urgent need for farmland protection and ecological compensation, this paper takes cultivated land as the research object and uses a three-dimensional ecological footprint model to account for and analyze the utilization of natural capital stock and flow of cultivated land in Beijing-Tianjin-Hebei region from 2009 to 2016 in terms of footprint breadth and depth, so as to provide reference for cultivated land protection, ecological compensation and even coordinated regional ecological-economic development. The results show that from 2009 to 2016, the ecological footprint breadth of cultivated land in Beijing-Tianjin-Hebei region was generally low and the footprint depth was generally high, and the ecological footprint depth of cultivated land in the region as a whole tended to increase, except for Zhangjiakou and Chengde, which were able to achieve self-sufficiency in flow capital, 85% of the cities showed the phenomenon of depletion of cultivated land flow capital and intensification of stock capital depletion. After 2010, the overall Gini coefficient of the ecological footprint of cultivated land in the Beijing-Tianjin-Hebei area was less than 0.4, and the use of natural capital from cultivated land was relatively balanced. The study concludes that under the strategic role of Beijing-Tianjin-Hebei integration and collaborative development, the equity of natural capital utilization of cultivated land in each city in the Beijing-Tianjin-Hebei region has been improved, but the level of creating and utilizing natural capital flows of cultivated land still needs to be improved, and ecological protection of cultivated land needs to be further strengthened; the excessive depletion of natural capital of cultivated land caused by agricultural production can be used as a reference basis for cross-regional ecological compensation of cultivated land, thus supporting the ecological value of cultivated land. Over-consumption of natural capital from agricultural land caused by agricultural production can be used as a baseline for interregional ecological compensation of agricultural land, thus supporting the realization of the ecological value of agricultural land.